Thermodynamic behavior of hydrophobically modified polyacrylamide containing random distribution of hydrophobes: experimental and theoretical investigations - Hourdet, Dominique; Ducouret, Guylaine; Varghese, Sony; Badiger, Manohar V.; Wadgaonkar, Prakash P. (Polymer, 2013)
Two series of Hydrophobically Modified Polyacrylamides (HMPAMs) were prepared by free radical copolymerization of trimethylsilylacrylamide with 3-pentadecylcyclohexylacrylamide (PDCAM) or dodecylacrylamide (DDAM) followed by removal of trimethylsilyl protecting groups. The solution properties of HMPAMs were studied in dilute aqueous solution by fluorescence spectroscopy, NMR and viscometry. The properties in aqueous solution of HMPAMs clearly displayed the formation of hydrophobic interactions between alkyl stickers. While dodecyl containing HMPAMs mainly showed a progressive collapse of the copolymer coil with the increasing fraction of hydrophobic moieties (weak intra-chain associations), pentadecylcyclohexyl groups containing HMPAMs exhibited a much lower solubility in water due to strong intra- and inter-chain associations. Experimental data were analyzed using the mean field theory developed by Semenov and Rubinstein (SR) for associating polymers. Using a set of realistic parameters, taking into account the solubility of the backbone, the fraction of stickers and the strength of hydrophobic attractions, we show that the SR model offers a quantitative description of the thermodynamic properties of HMPAMs in terms of individual and collective behavior of polymers chains; i.e. swelling and phase separation, respectively. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Polyacrylamide; Self-assembling

Thermoresponsive and biodegradable dextran based microgels: synthesis and structural investigation - Ghugare, Shivkumar V.; Chiessi, Ester; Sakai, Victoria Garcia; Telling, Mark T. F.; Wadgaonkar, Prakash P.; Paradossi, Gaio (Macromolecular Symposia, 2013)
Nanostructured objects, often ranging from hundreds of nanometers to few microns, support a number of functions directly linked to their structural features. They are, or they will be, protagonists in biomedical applications where miniaturized activities are required. These include the interface with living systems as tissues and cells, where targeted release of drug molecules occurs, or molecular imaging methods monitoring the drug trafficking in specific cell districts. The potentials of such devices, far to be fully understood, will be assessed only when a close correlation of their functions with their structure will be established. In this contribution we present a dextran based microdevice responsive to temperature and biodegradable. Both thermoresponsivity and biodegradability are of relevance for the potential use as drug carrier and controlled release device. The temperature behaviour, overall structure and internal architectures have been addressed with different methods.
Keywords: Biomaterials; colloids; dynamic light scattering; hydrogels; p(NiPAAm)

Tris-hydroxymethylaminomethane (THAM): a novel organocatalyst for a environmentally benign synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles - Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (New Journal of Chemistry, 2015)
simple, efficient and environmentally benign protocol has been developed for the one-pot, multicomponent synthesis of medicinally important tetrahydrobenzo[b]pyrans and pyran-annulated heterocycles using a commercially available, inexpensive, non-toxic, and biodegradable tris-hydroxymethylaminomethane (THAM) as a novel organocatalyst. Ambient reaction conditions, wide scope, avoidance of conventional isolation as well as purification techniques and the reusability of the catalyst for five consecutive runs have improved the practical utility of this multicomponent reaction protocol manifold.

Thermo-reversible sol-gel transition of aqueous solutions of patchy polymers - Parmar, Indravadan A.; Shedge, Aarti S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Lele, Ashish K. (RSC Advances, 2017)
While aqueous solutions of several amphiphilic thermo-reversible polymers show gelation upon heating, there are fewer examples of polymer solutions that exhibit gelation when cooled. This paper reports an interesting phenomenon of abrupt thermoreversible gelation of aqueous solutions of a hydrophobically modified polymer upon cooling. A high molecular weight precursor copolymer (PCP, (M-w) over bar approximate to 5 x 10(6) g mol(-1)) of N, N-dimethylacrylamide (70 mol%) and acrylic acid (30 mol%) was modified by reacting 10 mol% of the acrylic acid groups with n-dodecyl amine to form a hydrophobically modified copolymer (HMCP). The composition of the copolymer was ascertained using NMR spectroscopy. Cooling the solution of PCP at a controlled rate resulted in a gradual increase in its low shear viscosity as dictated by the flow activation energy. In contrast, cooling the solution of HMCP under identical conditions resulted in an abrupt and large non-Arrhenius increase in viscosity at a specific transition temperature, which decreased with decrease in polymer concentration. Fluorescence measurements and dynamic light scattering data showed that abrupt gelation happened upon cooling, when polymer coils percolate accompanied with concomitant transition in chain conformation from compact micellar coils formed by intra-chain hydrophobic associations to swollen polymer coils connected by inter-chain hydrophobic interactions.

Tris-hydroxymethylaminomethane (THAM): An efficient organocatalyst in diversity-oriented and environmentally benign synthesis of spirochromenes - Khot, Supriya S.; Anbhule, Prashant V.; Desai, Uday V.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2018)
Tris-hydroxymethylaminomethane has been demonstrated to be an efficient organocatalyst in diversity-oriented synthesis of medicinally prevalent spirochromenes by one-pot, three-component reactions between isatins, malononitrile, and enolizable CH acids like dimedone, 4-hydroxycoumarin, 4-hydroxy-N-methylquinolin-2-one, or in situ generated 2-methylpyrazolon-2-one. Biodegradability and extremely low cost of the catalyst are the noteworthy features of this chromatography-free protocol.
Keywords: green chemistry; Multicomponent synthesis; organocatalysis; Spirochromenes; Tris-hydroxymethylaminomethane

Thermally crosslinkable and chemically modifiable aromatic polyesters possessing pendant propargyloxy groups - Verma, Savita; Maher, Deepak M.; Nagane, Samadhan S.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
New aromatic (co)polyesters containing pendant propargyloxy groups were synthesized by phase transfer-catalyzed interfacial polycondensation of 5-(propargyloxy)isophthaloyl chloride (P-IPC) and various compositions of P-IPC and isophthaloyl chloride with bisphenol A. FTIR and NMR spectroscopic data, respectively, revealed successful incorporation of pendant propargyloxy groups into (co)polyesters and formation of (co)polyesters with desired compositions. (Co)polyesters exhibited good solubility in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran and could be cast into transparent, flexible, and tough films from chloroform solution. Inherent viscosities and number average molecular weights of (co)polyesters were in the range 0.77-1.33 dL/g and 43,600-118,000 g/mol, respectively, indicating the achievement of reasonably high-molecular weights. The 10% weight loss temperatures of (co)polyesters were in the range 390-420 degrees C, demonstrating their good thermal stability. (Co)polyesters exhibited T-g in the range 146-170 degrees C and T-g values decreased with increase in mol % incorporation of P-IPC. The study of non-isothermal curing by DSC indicated thermal crosslinking of (co)polyesters via propargyloxy groups. The utility of pendant propargyloxy group was demonstrated by post-modification of the selected copolyester with 1-(4-azidobutyl)pyrene, 9-(azidomethyl)anthracene, and azido-terminated poly(ethyleneglycol) monomethyl ether via copper(I)-catalyzed Huisgen 1,3-dipolar cycloaddition reaction. FTIR and H-1 NMR spectra confirmed that click reaction was quantitative. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 588-597
Keywords: Click chemistry; crosslinking; modification; polyesters; propargyloxy; step-growth polymerization